Density based traffic control system for a four way intersection - Chowdhury, Faizul Bari; Faruqui, Tahmid Azim; Razzaque, Rylah Marzia; Iqbal, Nayeem (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2023.